Does fluid bolus therapy increase blood pressure in children with sepsis?. (25th June 2019) - Long, Elliot; Babl, Franz E; Oakley, Ed; Hopper, Sandy; Sheridan, Bennett; Duke, Trevor; ,
Abstract: Objective: To describe the effect of fluid bolus therapy (FBT) on blood pressure in children with sepsis. Secondary outcomes included the effect of FBT on systemic vascular resistance, shock index and shock phenotype (warm or cold). Methods: This was a prospective observational study in the ED of The Royal Children's Hospital, Melbourne, Australia. Participants were children meeting international consensus criteria for sepsis who received FBT for tachycardia or hypotension. FBT was defined as 10–20 mL/kg of 0.9% saline. Mean blood pressure (MBP) was recorded at baseline, 5 and 60 min after FBT. Total systemic vascular resistance index (TSVRi), shock index, and shock phenotype were derived for each time point. Hypotension was defined as MBP <55 + 1.5 × age (years). Warm shock was defined as TSVRi <800 dyne s/cm 5 /m 2 . Results: Fifty fluid boluses were recorded in 41 children. Median MBP was 78 mmHg (interquartile range [IQR] 63–86) at baseline, 72 mmHg (IQR 60–82) at 5 min, and 75 mmHg (IQR 66–84) at 60 min. Hypotension was observed in 16% at baseline, 26% at 5 min and 17% at 60 min. Median TSVRi was 1580 dyne s/cm 5 /m 2 (IQR 1242–2206) at baseline, 1254 dyne s/cm 5 /m 2 (IQR 1027–1787) at 5 min, and 1850 dyne s/cm 5 /m 2 (IQR 1265–2140) at 60 min. Median shock index was 1.60 (IQR 1.34–1.90) at baseline, 1.49 (IQR 1.25–1.76) at 5 min and 1.37 (IQR 1.22–1.61) at 60 min. Two percent of cases had warm shock at baseline, 12% at 5 min and 2% at 60 min. Conclusions: MBP initially decreased following FBT for paediatric sepsis, returning towards baseline over the subsequent 60 min. The utility of FBT for increasing MBP and its effect on patient‐centred outcomes in children with sepsis warrants further exploration.